Design of Beam-Columns - Hooper, Ira (Engineering Journal, 1967)
The design of beam-columns in the 1963 AISC Specification recognizes two important features of structural behavior—frame stability and moment amplification due to lateral deflection. Frame stability may be defined as the ability of a structure to resist sidesway when vertical load is applied. It is not usually a problem for simply connected structures braced against sidesway. Old buildings have heavy masonry walls that provide bracing although no calculations were made for the bracing effect. Modern buildings can no longer afford the cost or wasted space of massive walls. Also, rigidly connected frames have become common. Rigidly connected frames offer several advantages: reduced beam deflections, greater economy and elimination of floor cracks.When rigidly connected frames are not braced against sidesway, the columns and beams must provide the stiffness needed to maintain frame stability in addition to their load resisting function.